Volcanic Evolution of the Southern Mountain Neogene Magmatic Belt in Baturagung Range Central Java, Indonesia - Mulyaningsih, Sri; Putong, Rahel; Prima, Anka; Hidayah, Radhtya Adzan; Kiswiranti, Desi (UIR PRESS, 2024)
Various Neogene volcanic rocks associated with calcareous sediments compose the Southern Mountain located from Imogiri at Yogyakarta to Wonogiri at Central Java, Indonesia. The volcanic rocks are concentrated along the north side of the Mountains which was recognized as the Neogene magmatic arc of Java; Baturagung is part of them. The discussion focuses on the relationship between the volcanic features and its basin evolution. The methods were geological fieldwork including measuring sections and collecting samples, thin sections, XRF, AAS, and micropaleontology. More than 13 circular hogbacks, circular valleys, and domes are observed based on the SRTM image. The petrology observed pyroxene-rich basaltic volcanic rocks, dacitic volcanic rocks, andesitic volcanic rocks, coral-rich volcanic breccia. From the bottom to the top, its stratigraphy of the Kebo-Butak Formation that notes basaltic volcanic rocks, pumice-rich lapillistone, and tuff of Early Neogene (before P4-N6) with muddy sandstone above the basalts of N 5-6 (Lower Miocene). The Semilir Formation consists of pumice-rich and dacitic tuff. Andesitic volcanic rocks of the Nglanggeran Formation with inlayer of marl of N 13-14. In the volcanic rocks trace elements show REE-rich (84-140 ppm), higher mobile elements of Sr ( 480-602 ppm), medium Rb (22.2-23.7 ppm), and medium La (12-21 ppm), and wide range of immmobile trace elements of Nb 2.7-7.9 ppm, Zr 53-171 ppm, P 840-1300 ppm, higher Ti (4400-4900 ppm), and higher Vanadium (V) of 92-302 ppm. Plot TiO2 vs. Al2O3 into the volcanic rocks indicates those were volcanism within plate boundaries. Plot Ta/Th vs Th/Hf shows continental extensional volcanism to continental arc margin. Plot Nb/Zr vs. Th/Zr explains the transitional zone to continental arc volcanism. The spider diagram shows Rb, Ce, P, Ti, Sr, Zr, and Y strongly metasomatized as a result of the upper continental arc. The chondrite normalized REE shows negative trends for Tb, Tm, Lu, Sm, and Eu and positive trends for Ce, Gd, Zr, and Y, which indicate superimposed volcanism under a submarine environment during the Neogene Period. Stratigraphic sections inform were periodically active volcanism. The Kebo-Butak Formation was formed by multiple volcanoes, some of which were active simultaneously while others were not, though both fall within the Early Neogene age range. Similarly, the Semilir and Nglanggeran Formations were also formed by volcanic activity from several volcanoes that were active at different times and overlapped with each other.